Prenatal invasive diagnostic testing for hemoglobinopathies: a retrospective cohort study at a tertiary care public hospital in central India - Gupta, Avantika; Gangane, Neha; Dhanvij, Minal; Davile, Medha; Mundle, Shuchita; Yadav, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Transfusion-dependent hemoglobinopathies such as sickle cell disease, thalassemia, etc. have a huge impact on the Indian economy due to the need for lifelong care and treatment of associated morbidities. Primary prevention strategies focus on awareness generation and pre-marital and pre-conceptional counseling to prevent the conception of a child with a homozygous genotype. Aim was to study the prevalence of carrier status of hemoglobinopathies, the couples at risk of carrying a fetus with major hemoglobinopathies, and the prevalence of fetal affection with major hemoglobinopathies in prenatal invasive testing. Methods: It was a retrospective cohort study conducted at AIIMS, Nagpur. Study conducted from 24 months (June 2021-June 2023). All antenatal women screened for hemoglobinopathies with HPLC and diagnosed to have hemoglobinopathies. Results: The 5,432 antenatal women were screened for hemoglobinopathy using high-performance liquid chromatography (HPLC). Out of these, 214 women were carriers of hemoglobinopathies. 53 couples were found to be at risk of carrying a fetus with major hemoglobinopathy. The 52 women underwent prenatal diagnosis (PND), 11 (21.1%) were found to be affected with major hemoglobinopathies and underwent medical termination of pregnancy (MTP). 24 babies were found to be carriers while 17 had no mutation. Conclusions: Owing to the high prevalence of hemoglobinopathies and the continually increasing impact on global health each year, the benefit of carrier screening programs to control incidence of new cases is recognized worldwide.